“Parenting” as the Enhancer of Subjective-Educative Experiences: Case Study on Parental Process of Children with Intellectual Disability - Sopingi, Sopingi (Journal of ICSAR, 2024)
From adults’ learning perspectives, parenting children with intellectual disabilities is considered a social reality interestingly researched, particularly related to the challenges and experiences during the parenting process encountered by parents who lack knowledge and understanding of intellectual disabilities. This research aims to (1) describe the configuration of parenting challenges in-depth and (2) explore the subjective-educative experiences derived from the challenges. This research was conducted using a qualitative approach with a phenomenological method. The data was derived from in-depth interviews with parents of children with moderate intellectual disability. The data were analyzed following the stages of the phenomenological method consisting of (1) description, (2) reduction, and (3) discovery of the main structure of meaning. The results show that (1) The challenges of the parenting process of children with intellectual disability require a high level of competence, encompassing both knowledge and technical parenting and psychological aspects, and (2) Various challenges in parenting children with disability lead to diverse subjective and educative experiences for parents. Based on the findings, this research recommends that parents continually improve parenting practices for children with intellectual disability by adhering to educational principles.